A Self-Efficacy Intervention to Improve Social Skills of Junior High School Students: A Systematic Review of 1 Decade - Pranowo, Taufik Agung; Halik, Al (Buletin Konseling Inovatif, 2025)
Social skills are an important aspect of the development of junior high school students, which are often hampered by low self-efficacy, affecting communication skills, social interaction, and conflict resolution. This study aims to evaluate the effectiveness of self-efficacy-based interventions in improving the social skills of junior high school students over the past decade (2013–2023). This study used a systematic review method with PRISMA guidance, including 28 studies that met the inclusion criteria, such as quasi-experimental research designs, valid and reliable instruments, and the population of junior high school students. Data were analyzed using narrative synthesis and meta-analysis to calculate the combined effects of self-efficacy interventions on social skills. The results showed that the self-efficacy intervention significantly improved students' self-efficacy, which had a positive impact on improving communication (+18%), social interaction (+15%), and conflict resolution ability (+20%). This intervention has also been shown to be effective in reducing social anxiety and bullying behavior by up to 25%. A holistic approach involving small group training programs and the integration of experiential learning showed superior results over other methods. The unique contribution of this study is its comprehensive scope, including the evaluation of moderation factors such as the duration of the intervention, participant characteristics, and the sustainability of the results. The study also highlighted the success of the intervention in specific subgroups, such as students with autism spectrum, which was previously underdiscussed. These findings offer new insights to develop more effective, directed, and inclusive self-efficacy-based intervention programs in supporting the social and emotional development of junior high school students.